Chlorophyll-a Concentration in Teluk Petai Lake Buluh Nipis Village Siak Hulu Sub District Kampar District Riau Province - M. Arifan Fadhilla M; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe research of chlorophyll-a concentration conducted in June-July 2020 at Teluk Petai Lake Buluh Nipis village. A study aims to understand the concentration and throphic state Teluk Petai lake based on chlorophyll-a . There were 3 stations namely station 1 (inlet area), station 2 (in the middle of the lake) and station 3 (in the end of the lake). In each stations vertically there were 2 sampling point, in the surface and 2 Secchi depth. Samplings were carried out three times with ten days interval. Result shown that temperature is 30-31oC, transparency 61.66-70 cm, pH 5, DO 4.17-5.23 mg/L, CO2 7.98-10.65 mg/L, nitrate 0.038-0.054 mg/L, phosphate 0.051-0.062 mg/L. Result shown that the chlorophyll-a concentration ranged from 7.63-14.37μg/L. Chlorophyll-a concentration influence the water quality such as transparency, nitrate and phosphate concentration. Based on the chlorophyll-a concentration, the waters at Teluk Petai lake can be categorized as mesothrophic. Keywords: Mesothrophic, Throphic State, Water Quality, Depth.